2011
DOI: 10.1007/s10722-011-9679-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome and genome composition of a Triticum × Thinopyrum hybrid by classical and molecular cytogenetic techniques

Abstract: Triticum-Thinopyrum amphiploids arose from the need to obtain forage grasses highly resistant to pest, drought, soil salinity and frost and they can be used as efficient bridges to transfer desired genes from wheatgrass species to wheat. One of them is trigopiro SH16 INTA, it was introduced in Argentina in 1947 but its genomic composition was unknown. The aim of this work was to determine the chromosome number and genomic and chromosome composition of trigopiro SH16 INTA in order to use it in breeding programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In previous studies, we have found that SH16 INTA is hexaploid, with 2n=42 chromosomes, 14 of which belong to the J genome of Thinopyrum and 28 to wheat genomes. We also found that 14 of the latter belong to genome B, 4 to genome D (chromosome pairs 2D and 4D) and the remaining ones probably to genome A (Fradkin et al, 2011).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In previous studies, we have found that SH16 INTA is hexaploid, with 2n=42 chromosomes, 14 of which belong to the J genome of Thinopyrum and 28 to wheat genomes. We also found that 14 of the latter belong to genome B, 4 to genome D (chromosome pairs 2D and 4D) and the remaining ones probably to genome A (Fradkin et al, 2011).…”
supporting
confidence: 51%
“…The cytogenetical results obtained in "trigopiro" Don Noé INTA showed important differences from those obtained in "trigopiro" SH16 INTA (Fradkin et al, 2011). Both hybrids currently used in breeding programs, present different levels of ploidy and different chromosome and genome composition.…”
Section: Resultsmentioning
confidence: 78%
“…Recombination of homoeologues also adds layers of genetic complication during the formation of amphidiploids, as the additional genome or genomes can be hybrids of the parental Thinopyrum genomes (Fedak and Han, 2005). There are several examples of lines stable at 42 chromosomes where a portion of the T. aestivum complement has been substituted with Thinopyrum chromosomes (Fradkin et al, 2011;Burešová et al, 2014). These lines are stable in meiosis but have not been evaluated for perennial habit.…”
Section: Hybrid Genomesmentioning
confidence: 99%
“…Processing quality can also be obtained from the decaploid A. elongatum [Liu et al, 2008]. Attempts were made to transfer traits such as perennial growth habit, winter hardiness, tillering, vigorous root development, and tolerance to salinity, drought, and disease from wheatgrass to cultivated wheat [White, 1940;Fradkin et al, 2012].…”
mentioning
confidence: 99%